FERDINAND DE SOSIR - 60 YEARS LATER - SINTAGMA VS. PHRASE. DISPUTED ELEMENTS IN THEIR INTERPRETATION (Živi jezici: Journal for Foreign Languages and Literatures, 2017)
This paper aims to explain the regularities in the structure of syntagms and phrases, to determine the common elements and differences between them, based on the teachings of Ferdinand de Saussure and his systemic character of language. The emphasis on the system should reveal whether different terminology is the product of different systems or different understandings of systems. The answer to this question would be of great help to children in school, confronted with the terms phrases and phrases, which often cause them problems.
Keywords: sintagma; phrase; superior word / nucleus; valence; dependent elements; morphosyntax; diagram